Application of the Pentahelix Model in the Preservation of Gibung Tradition to Increase the Attraction of Cultural Tourism in East Lombok - Mia Fidela; Ayuni Septiani Saputri; Tej Nafillah (Publikasi Indonesia, 2025)
The Gibung tradition in Kelayu is a cultural heritage of religious and social significance as a tribute to TGH Umar, a great local scholar. In addition to commemorating the haul of TGH Umar, this tradition strengthens social relations and maintains the cultural identity of the community